Morphology and developmental rate of blowflies Chrysomya megacephala and Chrysomya rufifacies in Thailand: Application in forensic entomology - Kom Sukontason (2018)
The larval morphology and developmental rate of Chrysomya megacephala (F.) and Chrysomya rufifacies (Macquart), the two most forensically important blowfly species in Thailand, are presented. Morphological comparison of the third instar of both species revealed different characteristics (e.g., body appearance, cephalopharyngeal skeleton, dorsal cuticular spines between the prothorax and mesothorax, and feature of the posterior spiracle), thereby, allowing correct identification. A data analysis was conducted in Chiang Mai province, Northern Thailand during 2000-2001 on the developmental rate of both flies under natural ambient temperature and a natural light-dark photoperiod. The results indicated that larvae of C. megacephala developed more rapidly in April, pupariation initiated at 84 h at temperatures averaging 31.4°C, and the larvae grew slower in the rainy season and winter. Similarly, rapid development of C. rufifacies larvae appeared in the summer, with a pupariation period as short as 96 h in June (average temperature 27.4°C). Analysis of the median body length of C. megacephala and C. rufifacies larvae in different seasons of the years 2000-2001 in Thailand revealed that both species developed rapidly in the summer; pupariation of C. rufifacies initiated at 144 h, while C. megacephala initiated pupariation at 156 h. This information is potentially useful for estimating the postmortem interval of a corpse in forensic investigations, where the corpse becomes infesting with these fly species. © 2008 Springer-Verlag.